Passive Constitutional Rights of Former Convictors in Regional Head Elections (Perspective of Constitutional Court Decision No. 42/PUU- XIII/2015) - Kurniawan, Anfal; Yudhanti, Ristina (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
This study discusses the political rights of former convicts to run as regional head candidates. This article is the result of an analysis of the Constitutional Court's decision No. 42/PUU-XIII/2015 which grants political rights to former convicts to run as regional head candidates. The basis for consideration (ratio decidendi) of the Constitutional Court's decision is; the right to vote and be elected can only be revoked based on a court decision, not based on statutory provisions; a person who has served a sentence and is released from prison is essentially a person who has repented and regrets his actions, so it is not appropriate to be given another punishment through statutory provisions that prohibit running in regional head elections. On that basis, the Constitutional Court grants the right to former convicts to run as regional heads. The Constitutional Court's decision has legal consequences for former convicts who were previously not allowed to run as regional head candidates. After the Constitutional Court's decision, convicts have the same rights to run in regional elections.